Nucleolar aggresomes mediate release of pericentric heterochromatin and nuclear destruction of genotoxically treated cancer cells - Salmina, Kristine; Huna, Anda; Inashkina, Inna; Belyayev, Alexander; Krigerts, Jekabs; Pastova, Ladislava; Vazquez-Martin, Alejandro; Erenpreisa, Jekaterina (Nucleus (Austin, Tex.), 2017)
The role of the nucleolus and autophagy in maintenance of nuclear integrity is poorly understood. In addition, the mechanisms of nuclear destruction in cancer cells senesced after conventional chemotherapy are unclear. In an attempt to elucidate these issues, we studied teratocarcinoma PA1 cells treated with Etoposide (ETO), focusing on the nucleolus. Following treatment, most cells enter G2 arrest, display persistent DNA damage and activate p53, senescence, and macroautophagy markers. 2-5 µm sized nucleolar aggresomes (NoA) containing fibrillarin (FIB) and damaged rDNA, colocalized with ubiquitin, pAMPK, and LC3-II emerge, accompanied by heterochromatin fragments, when translocated perinuclearly. Microscopic counts following application of specific inhibitors revealed that formation of FIB-NoA is dependent on deficiency of the ubiquitin proteasome system coupled to functional autophagy. In contrast, the accompanying NoAs release of pericentric heterochromatin, which exceeds their frequency, is favored by debilitation of autophagic flux. Potential survivors release NoA in the cytoplasm during rare mitoses, while exit of pericentric fragments often depleted of H3K9Me3, with or without encompassing by NoA, occurs through the nucleolar protrusions and defects of the nuclear envelope. Foci of LC3-II are accumulated in the nucleoli undergoing cessation of rDNA transcription. As an origin of heterochromatin fragmentation, the unscheduled DNA synthesis and circular DNAs were found in the perinucleolar heterochromatin shell, along with activation and retrotransposition of ALU elements, colocalized with 45S rDNA in NoAs. The data indicate coordination of the basic nucleolar function with autophagy regulation in maintenance of the integrity of the nucleolus associated domains secured by inactivity of retrotransposons.
Keywords: stárnutí buněk; NADs; Chromosomal Proteins, Non-Histone; inhibitor p16 cyklin-dependentní kinasy; autofagie; poškození DNA; LADs; nucleolus; DNA Damage; Cell Line, Tumor; rRNA transcription; Cell Nucleolus; ubiquitin-proteasome; ribozomální DNA; heterochromatin; kontrolní body buněčného cyklu; etoposid; Cellular Senescence; Mutagens; retroelementy; Retroelements; autophagy; mutageny; Cyclin-Dependent Kinase Inhibitor p16; pericentric fragments; Autophagy; lidé; Heterochromatin; Humans; chromozomální proteiny, nehistonové; ALU retrotransposition; Cell Cycle Checkpoints; cellular senescence; DNA, Ribosomal; nádorové buněčné linie; buněčné jadérko; Etoposide; aggresome